Bouveret Syndrome: A Rare Case of Gallstone Ileus Further Complicated by Stone Migration - Dunlop, Hannah (Cureus, 2020)
Bouveret syndrome is a rare cause of gastric outlet obstruction due to gallstone impaction in the pylorus or proximal duodenum. This paper reports a case of Bouveret syndrome in a 66-year-old male patient in whom pre-operative investigations revealed a gallstone within the distal stomach, but spontaneous migration of the stone resulted in intraoperative difficulty requiring further surgical exploration than originally anticipated.